2015
DOI: 10.1186/s12884-015-0473-8
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in severe postpartum hemorrhage: a nationwide comparative study of 1.6 million deliveries

Abstract: BackgroundThe incidence of severe postpartum hemorrhage (PPH) is increasing. Regional variation may be attributed to variation in provision of care, and as such contribute to this increasing incidence. We assessed reasons for regional variation in severe PPH in the Netherlands.MethodsWe used the Netherlands Perinatal Registry and the Dutch Maternal Mortality Committee to study severe PPH incidences (defined as blood loss ≥ 1000 mL) across both regions and neighborhoods of cities among all deliveries between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
2
11
5
Order By: Relevance
“…This is comparable with the literature where international prevalences of severe PPH varied from 0Á3 to 5Á1% (Africa) to 0Á7 to 2Á7% (Asia) and 1Á7 to 5Á5% (Europe) [7,8]. Consistent with other literature, we found regional differences in incidence of severe PPH in our retrospective study (Figure 1) [6,9]. This variation could not be explained by maternal and pregnancy characteristics, medical interventions or healthcare setting.…”
Section: Epidemiologysupporting
confidence: 92%
See 1 more Smart Citation
“…This is comparable with the literature where international prevalences of severe PPH varied from 0Á3 to 5Á1% (Africa) to 0Á7 to 2Á7% (Asia) and 1Á7 to 5Á5% (Europe) [7,8]. Consistent with other literature, we found regional differences in incidence of severe PPH in our retrospective study (Figure 1) [6,9]. This variation could not be explained by maternal and pregnancy characteristics, medical interventions or healthcare setting.…”
Section: Epidemiologysupporting
confidence: 92%
“…To measure the incidence of severe PPH in the Netherlands, we performed a retrospective study on prospectively collected data of all deliveries registered in the Netherlands Perinatal Registry in the period 2000-2008. We reported a national incidence of severe PPH (defined as ≥1000 ml blood loss) of 4Á5% of all deliveries for this period [6]. This is comparable with the literature where international prevalences of severe PPH varied from 0Á3 to 5Á1% (Africa) to 0Á7 to 2Á7% (Asia) and 1Á7 to 5Á5% (Europe) [7,8].…”
Section: Epidemiologysupporting
confidence: 86%
“…Postpartum haemorrhage is the leading cause of almost a quarter of all maternal deaths worldwide . The incidence of severe primary PPH (≥1000 mL blood loss within 24 h postpartum) in the general Dutch population is 4.5% . In a previous study of our group, 51% of women with moderate and severe VWD self‐reported PPH ; other studies documented an incidence of 20–40% in VWD and carriers of haemophilia .…”
Section: Introductionmentioning
confidence: 51%
“…Massive or severe PPH is defined variously as a blood loss ≥ 1,000 ml 4,7,8 or ≥ 1,500 ml 9,10 ; bleeding requiring a blood transfusion 5 ; or bleeding requiring ≥ 8 bags of red blood cells 11,12 . The average rate for severe PPH is 1.2%, with a range of 0.02-4.5%, depending on how PPH is defined 4,5,[7][8][9][10][11][12] . The most common cause of severe PPH, responsible for 27% of all maternal deaths 2 , is uterine atony, which is the failure of the uterus to contract after the birth of a baby 4 .…”
Section: Introductionmentioning
confidence: 99%